The effect of the first vaginal birth on pelvic floor anatomy and dysfunction - Urbankova, Iva; Grohregin, Klara; Hanacek, Jiri; Krcmar, Michal; Feyereisl, Jaroslav; Deprest, Jan; Krofta, Ladislav (International urogynecology journal, 2019)
INTRODUCTION AND HYPOTHESIS: First vaginal delivery severely interferes with pelvic floor anatomy and function. This study determines maternal and pregnancy-related risk factors for pelvic floor dysfunction (PFD), including urinary incontinence (UI), urgency, anal incontinence (AI), pelvic organ prolapse (POP) and levator ani muscle (LAM) avulsion. METHODS: This is a single-centre prospective observational cohort study on healthy women in their first singleton pregnancy. All underwent clinical and 3D transperineal ultrasound examination at 6 weeks and 12 months postpartum. Objective outcomes were POP-Q and presence or absence of LAM trauma. Functional outcomes were measured by the ICIQ-SF and PISQ 12. Multivariate regression was performed to determine birth and maternal habitus-related risk factors for UI, urgency, AI, dyspareunia, LAM avulsion and ballooning. RESULTS: Nine hundred eighty-seven women were included. Risk factors for UI were maternal age per year of age (OR: 1.09; 95% CI: 1.04-1.13; p = 0.0001) and BMI before pregnancy (OR: 1.08; 95% CI: 1.04-1.13; p = 0.001); for POP stage II+ maternal age (OR: 1.08; 95% CI: 1.08-1.14; p = 0.005). Avulsion was more likely after forceps (OR: 3.22; 95% CI:1.54-8.22; p = 0.015) but less likely after epidural analgesia (OR: 0.58; 95% CI: 0.37-0.90; p = 0.015) and grade I perineal rupture (OR: 0.50; 95% CI: 0.29-0.85; p = 0.012). Ballooning was more likely at increased maternal age (OR: 1.08; 95% CI: 1.02-1.13; p = 0.005), epidural (OR: 1.64; 95% CI: 1.06-2.55; p = 0.027) and grade I perineal rupture (OR: 1.79; 95% CI: 1.10-2.90; p = 0.018). CONCLUSION: Though maternal characteristics at birth such as age or BMI increase the risk of PFD, labour and birth factors play a similarly important role. The most critical risk factor for MLA avulsion was forceps delivery, while an epidural had a protective effect.
Keywords: Pelvic organ prolapse; Incontinence; Pregnancy; Humans; porod; Female; dospělí; onemocnění dna pánevního; Pelvic Floor Disorders; Forceps; Maternal age; lidé; inkontinence moči; Fecal Incontinence; fekální inkontinence; Parturition; Urinary Incontinence; parita; Adult; ženské pohlaví; vedení porodu; Delivery, Obstetric; Parity; těhotenství; prospektivní studie; BMI; Prospective Studies